Radiation Recall Pneumonitis Induced by Sintilimab: A Case Report and Literature Review - Wang, Min; Xu, Shuhui; Zhu, Hui (Frontiers in Immunology, 2022)
Radiation recall pneumonitis (RRP) is described as an unpredictable acute inflammatory reaction within the previously irradiated lung site during the administration of systematic therapy after radiotherapy. Here, we reported a case of a 54-year-old woman with non-small lung cancer (NSCLC), who had pneumonitis at 3 and 10 months after radiotherapy regarded as radiation pneumonitis (RP) and RRP induced by anti-PD-1 sintilimab, respectively. This unique patient with double pneumonitis (RP and RRP) has drawn attention to the identification of immune or radiation pneumonitis, its potential mechanism, and further treatment strategy after the emergence of RRP.